Hubungan Variabel yang Mempengaruhi Kurangnya Minat Masyarakat Surabaya Memilih Asuransi Syariah - Hanifah Saputri, Safhira Evani; Indrarini, Rachma (Universitas Negeri Surabaya, 2020)
The low interest of Surabaya people to sharia insurance resulted in the development of sharia insurance. So this research aims to know whether there is a relationship between variable product, price, place, promotion, people, process, and physical evidence with a lack of interest in Surabaya people choose sharia insurance. This research is a correlation study using quantitative methods measured by the likert scale and analyzed using spss version 23. The result showed that only one variable of research showing the relationship with lack of interest in Surabaya people choose sharia insurance, which is price variable